THEORETICAL METHODOLOGY OF STUDYING THE LANGUAGE SOUND SYSTEM (Scientific journal of the Fergana State University, 2023)
In this article, it has been informed about the phonetic system of Uzbek and English languages, with the main focus on the vocalic system.